Accelerated creep and creep-rupture testing of transverse unidirectional carbon/epoxy lamina based on the stepped isostress method. (1st January 2017) - Tanks, Jonathon; Rader, Katherine; Sharp, Stephen; Sakai, Takenobu
Abstract: Accelerated methods for measuring long-term viscoelastic properties of fiber reinforced polymer (FRP) composites are important for reducing the time needed to characterize material behavior. Most of them are based on the time-temperature-stress superposition principle (TTSSP), or some variation. This paper investigates the applicability of the stepped isostress method (SSM) to study tensile creep of unidirectional carbon FRP (CFRP) lamina used in rehabilitating prestressed concrete structures. The SSM employs a load-stepping approach, typically with three to five steps for a single specimen resulting in creep-rupture. Theoretical analysis of the experimental method (previously lacking) is discussed and modifications to the testing and analysis protocol are shown to improve validity of the master curves compared to conventional creep curves and traditional TTSSP creep master curves at room temperature. Finally, three failure criteria are compared for predicting creep-rupture of CFRP laminates based on the accelerated testing method.